Pendidikan Modern: Kajian Terhadap Universitas Al-Azhar dan Pembaharuan Pendidikan Di Mesir - Rinjani, Cintia; Napu, Helmi (Institut Agama Islam Sumatera Barat Pariaman, 2022)
The purpose of this study is expected to contribute to an understanding of the social history of Islamic education regarding the al-Azhar educational institution. The method used is Library Research or library analysis, data collection is carried out through a systematic search of scientific literature on book articles and related documents. The development of Al-Azhar Islamic education did not escape the influence of the related social history at that time. The social history of Islamic education in the reform and modern era at Al-Azhar can be concluded in several ways. First, the social background of al-Azhar and the emergence of Napoleon Bonaparte who later ruled Egypt. Second, the shift of Shi'i rational understanding to orthodox Sunni ideology. Third, French Civilization which Napoleon brought to his education at Al-Azhar. Fourth, the figures and ideas for renewal at Al-Azhar pioneered by Muhammad Ali Pasha, Muhammad Abduh, Muhammd Rasyid Rida.